Digital Entrepreneurship, Gender and Intersectionality An East Asian Perspective - Leung, Wing-Fai.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Palgrave Macmillan, 2019)
This book details qualitative research focusing on Internet startups, digital entrepreneurship, race and sex discrimination, and the sharing economy. Addressing the intersections between issues of gender, age, ethnicity and class, the author interviews startup founders, including many husband and wife teams, in order to understand the working and private lives of digital entrepreneurs in and from Taiwan who utilise Internet and mobile technologies, against a backdrop of the country's political, social and economic history. It investigates contemporary debates about entrepreneurship as they are experienced by new generations of start-uppers who challenge existing social and cultural norms by becoming creative workers and embracing the precarity that exists in the volatile digital economy.
1. Introduction -- 2. Family Metaphor, the Geek and the Entrepreneurial Ideal -- 3. Girls in Tech: Progress and Barriers in a Gendered Culture -- 4. Luxury Chairs and Pizzas: The Production of Social Spaces and Class -- 5. Cool, Creative but not so Equal -- 6. Conclusions.
Keywords: Industrial sociology; Sex; Mass media; Digital media; Entrepreneurship; New business enterprises; Sociology of Work; Gender Studies; Media Sociology; Digital and New Media; Entrepreneurship